Strength and conditioning. A biomechanical approach - Moir, G. L. (Jones & Bartlett Learning, 2016)
Chapter 1 Basic Mechanics: Kinematic Variables Chapter 2 Basic Mechanics: Kinetic Variables Chapter 3 Structure and Mechanical Function of Skeletal Muscle and Tendon Chapter 4 Bioenergetics of Exercise Chapter 5 Muscular Strength and Power Chapter 6 Training Methods to Develop Muscular Strength and Power Chapter 7 Training Methods to Develop Flexibility Chapter 8 Warm-up Methods Chapter 9 Performance Analysis in Sport Chapter 10 Skill Acquisition Chapter 11 Biomechanics of Fundamental Movements: Jumping Chapter 12 Biomechanics of Fundamental Movements: Landing Chapter 13 Biomechanics of Fundamental Movements: Sprint Running